Epistemic uncertainty and the support of productive struggle during scientific modeling for knowledge co‐development - Chen, Ying‐Chih (Journal of research in science teaching, 2022)
There is a considerable amount of research on the nature and effectiveness of modeling as applied to student learning in science. However, few studies have examined the role of students' epistemic uncertainty in modeling and how teachers collaborate with students to recognize and utilize it as a pedagogical resource to support productive struggle for the co‐development of scientific knowledge. This single case study focuses on how one fifth‐grade teacher and her students used epistemic uncertainty as a resource to engage in modeling as they co‐developed knowledge through building, revising, and finalizing models. Data were collected 16 lessons across 4 weeks when students learned the role of the respiratory system in the breathing process. Multiple strategies to manage students' epistemic uncertainty for productive struggle were identified across four phases of modeling. Phase 1, Problematizing a phenomenon: using student epistemic uncertainty to contextualize and format a problem, Phase 2, Material practice: recognizing and supporting student epistemic uncertainty that may cause struggle, failure, and opportunity for rebuilding a model, Phase 3, Argumentative practice: critiquing and decomposing student epistemic uncertainty to find possible solutions, and Phase 4, Conceptualizing theory and application of final models: having students use different representations of their final models to theoretically explain the target phenomenon. By providing an empirical account of the evolution of students' knowledge co‐development, this study suggests that productive modeling should encompass the variation of student epistemic uncertainties as an effective resource to cumulatively engage students through the different phases of modeling in the productive struggle to sense‐make and develop a coherent understanding of scientific knowledge and practice. As such, students have opportunities to reflect on and generate their own knowledge in the sensemaking process, rather than just replicate knowledge from textbooks or authorities.